Internal Marketing to face the "new normal" workplace challenges: Organizational Agility as a booster - Nancy Berenice Ortiz Alvarado; Eva María Guerra Leal (Ciencias Administrativas Teoría y Praxis, 2022)
The purpose of this research is to identify the new challenges and opportunities that companies had faced due to the radical transformation of work schemes during the COVID-19 contingency. During this environment of uncertainty and change, we look for an understanding of how organizational agility has helped companies to implement key Internal Marketing strategies to cope with such challenges, being able to differentiate between “brilliant improvisation” and a repeatable capability to be prepared for a future crisis or environmental challenging scenarios. This paper presents a proposed model that analyzes two relevant research gaps: 1) The relationship between Internal Marketing and Organizational Agility, and 2) The challenges of Internal Marketing inside an organization derived from an external crisis (COVID-19). Eight semi‐structured long interviews, focused on understanding the employer's perspective, were developed with CEOs of SMEs in various industries in Mexico. The findings suggest five main challenges to enable Internal Marketing strategies through organizational agility: 1) communication 2) emotional well-being, 3) safety, 4) empowerment, and 5) digital tools management.